Budget accommodation in Singapore : a demand and supply perspective. - Chay, Sau Fong. (2008)
Tourism has always been one of the key economic drivers in Singapore. Hotel average occupancy rates reached a record high of 91% in July 2006 and are projected to be high over the next few years. This research aims to find out the market potential of the budget accommodation (BA) segment and the business strategies of the existing BAs in Singapore.